BRAF and MEK inhibitors rechallenge after an adverse drug reaction in patients with cancer: A pharmacovigilance cohort study - Ezine, Emilien; Silva, Angélique Da; Idoudi, S.; Lebbé, Célèste; Chrétien, Basile; Sassier, Marion; Alexandre, Joachim; Dolladille, Charles (Therapies, 2025)
IMPORTANCE: The safety profile of a rechallenge with BRAF inhibitors (BRAFi) or a combination of BRAF and MEK inhibitors (MEKi) following an adverse drug reaction (ADR) remains largely unexplored. OBJECTIVE: To identify the reported recurrence rate of the same ADR after a BRAFi±MEKi targeted therapy (TT) rechallenge in patients with cancer and to identify factors associated with recurrence. DESIGN, SETTING, AND PARTICIPANTS: In this observational, pharmacovigilance study, ADR reports were sourced from VigiBase, the World Health Organization database. The inclusion criteria encompassed all BRAFi cases (with or without MEKi) through September 01, 2023, irrespective of the primary cancer diagnosis. MAIN OUTCOMES AND MEASURES: The primary outcome was the reported recurrence rate of the same initial ADR following TT rechallenge. Secondary outcomes measures included were identification of variables associated with recurrence among informative rechallenges, defined as those with known recurrence status. RESULTS: Out of 21,339 ADR cases linked to TT, 4771 (22.4%) reported a rechallenge, with 563 yielding informative data (11.8%). Recurrence of the initial ADR was reported in 223 cases, resulting in a reported recurrence rate of 39.6% (95% CI: 35.7-43.7). The highest recurrence rates in a rechallenge were observed for pyrexia (47%, 95% CI: 39-55), renal failure (46%, 95% CI: 32-60), and musculoskeletal disorders (44%, 95%CI: 33-56). There was no significant influence of factors such as TT regimen (either BRAFi monotherapy or any TT combination), age, sex, or the type of cancer on reported recurrence rate. CONCLUSIONS AND RELEVANCE: In real-world settings, approximately two-fifths of cases with notified TT rechallenges led to a reporting of recurrence of the same initial ADR. The primary determinant of reported recurrence seems to be the nature of the initial ADR rather than the TT regimen, or any other baseline patient characteristic.